'I still want to tell stories': an interview with Jerry Ordway. Issue 2 (3rd March 2020) - Klaehn, Jeffery
ABSTRACT: Jerry Ordway is a comic book artist, painter, writer and inker widely known for his work on the "Death of Superman" storyline and the original Captain Marvel (Shazam) at DC Comics. This interview explores his career in comics to date, from his discovery of fanzines in the early 1970s to his career-defining work on All-Star Squadron, Infinity Inc., Fantastic Four, Superman, The Power of Shazam!, and his creator-owned properties, Proton, The Messenger, and (with Alex de Campi) Semiautomagic .